Population, Population Density, and Technological Change - Stephan Klasen; Thorsten Nestmann (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2004)
In a model on population and endogenous technological change, Kremer combines a short-run Malthusian scenario where income determines the population that can be sustained, with the Boserupian insight that greater population spurs technological change and can therefore lift a country out of its Malthusian trap. We show that a more realistic version of the model, which combines population and population density, allows deeper insights into these processes. The incorporation of population density also allows a superior interpretation of the empirical regularities between the level of population, population density, population growth, and economic development, both at aggregated and disaggregated levels.
Keywords: N3; J1; O3; 330; Bevölkerungsökonomie; Bevölkerungsentwicklung; Bevölkerungsdichte; Endogener technischer Fortschritt; Technischer Fortschritt; Theorie; Welt